Metabolic Labeling with an Alkyne-modified Isoprenoid Analog Facilitates Imaging and Quantification of the Prenylome in Cells - Palsuledesai, Charuta C; Ochocki, Joshua D; Kuhns, Michelle M; Wang, Yen-Chih; Warmka, Janel K; Chernick, Dustin S; Wattenberg, Elizabeth V; Li, Ling; Arriaga, Edgar A; Distefano, Mark D (ACS chemical biology, 2016)
Protein prenylation is a post-translational modification that is responsible for membrane association and protein–protein interactions. The oncogenic protein Ras, which is prenylated, has been the subject of intense study in the past 20 years as a therapeutic target. Several studies have shown a correlation between neurodegenerative diseases including Alzheimer’s disease and Parkinson’s disease and protein prenylation. Here, a method for imaging and quantification of the prenylome using microscopy and flow cytometry is described. We show that metabolically incorporating an alkyne isoprenoid into mammalian cells, followed by a Cu(I)-catalyzed alkyne azide cycloaddition reaction to a fluorophore, allows for detection of prenylated proteins in several cell lines and that different cell types vary significantly in their levels of prenylated proteins. The addition of a prenyltransferase inhibitor or the precursors to the native isoprenoid substrates lowers the levels of labeled prenylated proteins. Finally, we demonstrate that there is a significantly higher (22%) level of prenylated proteins in a cellular model of compromised autophagy as compared to normal cells, supporting the hypothesis of a potential involvement of protein prenylation in abrogated autophagy. These results highlight the utility of total prenylome labeling for studies on the role of protein prenylation in various diseases including aging-related disorders.